2021
DOI: 10.48550/arxiv.2111.07768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can angular oscillations probe superfluidity in dipolar supersolids?

Matthew A. Norcia,
Elena Poli,
Claudia Politi
et al.

Abstract: Angular oscillations can provide a useful probe of the superfluid properties of a system. Such measurements have recently been applied to dipolar supersolids, which exhibit both density modulation and phase coherence, and for which robust probes of superfluidity are particularly interesting. So far, these investigations have been confined to linear droplet arrays. Here, we explore angular oscillations in systems with 2D structure, which in principle have greater sensitivity to superfluidity. Surprisingly, in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 22 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Let us consider the supersolid "zig-zag" configuration shown in Fig. 1 (d) corresponfing to dd = 1.466, which is close to the value considered in the recent experiment of [25]. In the inset of Fig.…”
Section: Numerical Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…Let us consider the supersolid "zig-zag" configuration shown in Fig. 1 (d) corresponfing to dd = 1.466, which is close to the value considered in the recent experiment of [25]. In the inset of Fig.…”
Section: Numerical Resultsmentioning
confidence: 71%
“…This was actually the procedure followed in [15]. As explicitly pointed out in [25] the situation is different in more two-dimensional configurations, characterized by a smaller deformation of the density profile. In [25] it was actually found that the frequency of the dominant oscillation, following the sudden release of the trap, is close to the irrotational value (3) even for configurations where the moment of inertia deviates from the irrotational value in a significant way, therefore raising the question whether the experimental measurement of the scissors mode can in general provide a measure of the moment of inertia and of the superfluid nature of the system.…”
Section: Sum Rules and Linear Response Approachmentioning
confidence: 92%
See 3 more Smart Citations